Paths to Success: The Relationship Between Human Development and Economic Growth. - Boozer, M; Ranis, G; Stewart, F; Suri, T (Economic Growth Center (Yale University), 2003)
This paper explores the two-way relationships between Economic Growth (EG) and Human Development (HD), building on an earlier work by Ranis, Stewart, and Ramirez (2000). Here, we show that HD is not only a product of EG but also an important input to it. The paper develops new empirical strategies to estimate the strength of the two-way chains connecting HD and EG. Building on existing growth literature, we explore the empirical determinants of positive growth trajectories running from HD to EG and find that HD plays an essential role in explaining growth trajectories. Our findings point to the empirical relevance of endogenous growth models in general, and threshold effect models in particular. We also develop a measure of the strength of the EG to HD relationship and explore some of its empirical determinants. A strong sequencing implication of our findings is that HD must be given priority for the achievement of both higher EG as well as HD.